Pengaruh Penggunaan Model Problem Based Learning Terhadap Minat Belajar PAK Siswa Kelas VIII SMP Negeri 1 Sipoholon Kabupaten Tapanuli Utara Tahun Pembelajaran 2022/2023 - Jodi Andreas Manullang; Andar Gunawan Pasaribu; Robert K.A Simangunsong (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The research aims to determine the positive and significant influence of using the problem based learning model on the interest in learning PAK of class VIII students at SMP Negeri 1 Sipoholon for the 2022/2023 academic year. The research hypothesis is that there is a positive and significant influence between the use of the problem based learning model on the interest in learning PAK of class VIII students at SMP Negeri 1 Sipoholon for the 2022/2023 academic year. This research is a regression research using Descriptive and Inferential Statistics techniques. The population of all class VIII students at SMP Negeri 1 Sipoholon who are Protestant Christians is 190 people. Random sampling (random sampling) is 25% of the total population, namely 48 people. The research instrument is a closed questionnaire. From the determination coefficient test, the value r2 = 0.2520 is obtained. From the determination value (r2), it can be seen that the percentage of influence between the use of the problem based learning model on the interest in learning PAK of class VIII students of SMP Negeri 1 Sipoholon for the 2022/2023 academic year is 25.20% and 74 .80% is influenced by other factors as explained in the literature review, namely factors in the school environment, factors in the home environment, factors in the community environment. The results of the analysis requirements obtained the value rxy=0.502>rtabel=0.284 and tcount=3.937>ttable=2.021, indicating that there is a relationship between the use of the problem based learning model and students' interest in learning PAK and obtaining the regression equation. Hypothesis testing obtained Fcount=52.15>Ftable=3.23, so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the use of the problem based learning model on the interest in learning PAK of class VIII students at SMP Negeri 1 Sipoholon for the 2022/2023 academic year of 25.20%.